A comparison of the efficacy of calcium hydroxide, iodine potassium iodide and chlorhexidine on Actinomyces israelii contaminated dentinal tubules using an in vitro model - Tait, Carol Margaret Elizabeth (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc.) -- University of Stellenbosch, 1998.